Pengaruh Kinerja Lingkungan Dan Intellectual Capital Terhadap Kinerja Keuangan (Studi Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022) - Agustina, Ira; Effendy, Lukman (Jurnal Riset Mahasiswa Akuntansi, 2024)
This research aims to determine the influence of environmental performance and intellectual capital on the financial performance of mining companies listed on the Indonesian Stock Exchange (BEI) in 2018-2022. The independent variables in this research are environmental performance which is measured using the PROPER rating, and intellectual capital is measured using the Value Added Intellectual Coefficient (VAICTM). The dependent variable in this research is financial performance measured using return on assets (ROA). The sampling method used purposive sampling so that the sample obtained was 24 company data. The data analysis technique uses panel data regression analysis with the eviews 12 application. The research results show that environmental performance has no effect on financial performance, and intellectual capital has no effect on financial performance.